1996
DOI: 10.1159/000126973
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-Pituitary-Adrenal Response to Chronic Stress in Five Inbred Rat Strains: Differential Responses Are Mainly Located at the Adrenocortical Level

Abstract: The effects of chronic stress on the hypothalamic-pituitary-adrenocortical (HPA) axis were studied in five inbred rat strains, i.e. Brown Norway (BN), Fischer (FIS), Lewis (LEW), Spontaneously Hypertensive (SHR) and Wistar Kyoto (WKY). Previously, these rat strains had been shown to display clear behavioral differences in the forced swimming test that presumably measures depression-like behavior, BN and WKY being more passive than the other strains. Here we test the hypothesis that the differences in behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
137
4
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(160 citation statements)
references
References 54 publications
17
137
4
1
Order By: Relevance
“…This may, in at least part, explain the lack of significant difference in CS levels between the groups. However, importantly, the results confirm that the CS doses used in this study produced plasma levels that were within the physiological range, and appropriate to those that are seen in chronic stress in rats (Gomez et al, 1996). Two other studies have shown that adrenalectomy inhibits epileptogenesis in the kainic acid (Lee et al, 1989) and kindling (Karst et al, 1997) rat models.…”
Section: Discussionsupporting
confidence: 83%
“…This may, in at least part, explain the lack of significant difference in CS levels between the groups. However, importantly, the results confirm that the CS doses used in this study produced plasma levels that were within the physiological range, and appropriate to those that are seen in chronic stress in rats (Gomez et al, 1996). Two other studies have shown that adrenalectomy inhibits epileptogenesis in the kainic acid (Lee et al, 1989) and kindling (Karst et al, 1997) rat models.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, differences in the stress-induced plasma corticosterone level in various genetically defined strains of rat are suggested to arise from differences in adrenal sensitivity to ACTH, rather than differences in pituitary ACTH secretion (Gmez et al, 1996;Sarrieau et al, 1998). However, if differences in interrenal sensitivity underlie the divergent stress responsiveness of the HR and LR lines, this is not reflected in plasma cortisol levels in unstressed fish.…”
Section: Discussionmentioning
confidence: 99%
“…40 Importantly, the increased immobility in WKY rats in the FST does not appear to be a result of impaired cognitive or motor abilities. 41 In addition to depressive-like behaviors, WKY rats exhibit alterations of the HPA axis, including greater increases in plasma adrenocorticotropin hormone (ACTH) secretion after acute stress, 31,33,[42][43][44] and a decrease 32,45 or no change 26,31,43,46 in stress-induced corticosterone (CORT) levels relative to other rat strains. Alterations of the 24-h diurnal secretion pattern of plasma ACTH and CORT are also observed in WKY relative to Wistar rats.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the inbred F344 rat does not exhibit depressive-like behavior 27 and both basal and poststress levels of CORT differ from those found in the WKY. 32,44 In the present study, we have measured both immobility and climbing in the FST as indicators of depressive-like behavior. We have also examined three aspects of the HPA axis, all of which are altered in major depression and are controlled by different mechanisms:(1) basal plasma CORT levels, (2) plasma CORT levels in response to acute stress and (3) adrenal weight.…”
Section: Introductionmentioning
confidence: 99%